2021
DOI: 10.3390/ijms22073363
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl Trisulfide Diminishes Traumatic Neuropathic Pain Acting on TRPA1 Receptors in Mice

Abstract: Pharmacotherapy of neuropathic pain is still challenging. Our earlier work indicated an analgesic effect of dimethyl trisulfide (DMTS), which was mediated by somatostatin released from nociceptor nerve endings acting on SST4 receptors. Somatostatin release occurred due to TRPA1 ion channel activation. In the present study, we investigated the effect of DMTS in neuropathic pain evoked by partial ligation of the sciatic nerve in mice. Expression of the mRNA of Trpa1 in murine dorsal-root-ganglion neurons was det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 69 publications
1
12
0
Order By: Relevance
“…Our study confirmed that DMTS is a potent agonist of TRPA1 channels [15,27]. We demonstrated that DMTS mitigated edema formation and plasma extravasation in the K/BxN serum-transfer arthritis model as well.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our study confirmed that DMTS is a potent agonist of TRPA1 channels [15,27]. We demonstrated that DMTS mitigated edema formation and plasma extravasation in the K/BxN serum-transfer arthritis model as well.…”
Section: Discussionsupporting
confidence: 82%
“…The control animals received nonarthritogenic BxN serum. DMTS (Sigma-Aldrich, Budapest, Hungary) solutions were prepared as described earlier [27]. The stock solution was prepared in dimethyl sulfoxide (Reanal, Budapest, Hungary; 1 mol/L), and was diluted 10× with saline containing polysorbate 80 (0.9% m/v NaCl and 2% v/v polysorbate 80; 100 mmol/L DMTS).…”
Section: Induction Of Serum-transfer Arthritis and Treatment With Dmtsmentioning
confidence: 99%
“…Over the past years, the in situ hybridization-based technique RNAscope has been increasingly used in research and clinical studies due to its sensitivity and specificity, which have been evaluated in the context of pathologic diagnostics. 21 23 RNAscope has been used to evaluate TRPA1 and TRPV1 mRNA abundance in neuronal cells from the peripheral 24 26 and the central nervous system, 27 29 as well as non-neuronal tumor cells. 30 However, whether there is a correlation between mRNA and functional responses has not been assessed before.…”
Section: Discussionmentioning
confidence: 99%
“…NP is defined by the International Association for the Study of Pain as “pain caused by a lesion or disease of the somatosensory nervous system” [ 86 ]. There is growing evidence that TRPA1 plays an important role in different patterns of NP progression, such as traumatic NP [ 87 ], chemotherapeutic-induced NP [ 88 ], and diabetic NP [ 89 ]. MicroRNAs (miRs) are small non-coding endogenous RNA molecules that inhibit their target mRNAs by binding complementarily in the informative 3′-UTR [ 90 ].…”
Section: Discussionmentioning
confidence: 99%